Electrochemical reduction of CO2 on core-shell Cu/Au nanostructure arrays for syngas production. (10th June 2017) - Chen, Kun; Zhang, Xinyi; Williams, Tim; Bourgeois, Laure; MacFarlane, Douglas R.
Graphical abstract: Highlights: Synthesis of highly ordered Cu nanowires using anodic aluminium oxide template. Achievement of an unprecedented high current among metal electrodes for CO2 reduction. Detailed investigations of core-shell Cu/Au nanostructure arrays for syngas production. Demonstration of stable CO/H2 ratio over a long period of time. Abstract: Electrocatalytically converting CO2 to hydrocarbons is a very attractive way to use the excess electricity generated from renewable energies. In this paper, we report the electrochemical reduction of CO2 based on Cu nanowire arrays. The Cu nanostructured electrode shows much higher current density than polycrystalline Cu. By sputter coating a thin layer of Au on the Cu nanowires, the Faradaic efficiency (FE) of CO can exceed 30%. At an overpotential of 540 mV with respect to the formation of CO, the Cu/Au core-shell nanowire array electrode catalyses the formation of syngas, a very useful gas mixture, with a stable CO/H2 ratio.